Placardes and Billis and Ticquettis of Defamatioun': Queen Mary, the Mermaid and the Hare. (18th December 2015) - Bath, Michael; Jones, Malcolm
Placards circulating in Edinburgh following the murder of Henry Darnley in 1567, depicting Queen Mary as a seductive mermaid and Darnley as a timid but lecherous hare, are shown to copy details from two emblems in Claude Paradin's Devises heroïques. Once stripped of their Latin mottoes, these emblems are not easy to make sense of, and the two variant copies of the placards which are preserved in the English National Archives at Kew raise issues of meaning, form and function surrounding such public documents, which are explored in this article. The historical circumstances of their display in Scotland are examined, together with documents identifying James Murray as their 'deviser'. This leads to a wider discussion of the place of emblems in Scottish culture at this period in relation to other forms of political and judicial publication, variously known as 'placards', 'bills', 'libels', German 'Schandbilder' and Scots 'baffles', these being genres which have not hitherto been identified as strongly emblematic or indebted to printed emblem books. The scholarly and often erudite basis of emblems is always likely to have problematised their use in such popular, public displays, and the iconography of the 'Mermaid and Hare' must not only have challenged early viewers unfamiliar with the emblems on which it was based, but remains unclear in a few of its details even now when its sources in Paradin have been identified. Its political effectiveness in its own day is not, however, in doubt.